Synthesis of bimetallic CoMn–alginate and synergistic effect on thermal decomposition of ammonium perchlorate. (September 2019) - Lu, Yuewen; Wang, Ruihao; He, Jiexin; Xu, Pengfei; Li, Hua; Tian, Lu; Guo, Changping
Graphical abstract: Highlights: CoMn-alginate/AP composite was successfully prepared by a facile approach. CoMn-alginate had a 3D network structure with pores and some thin nanosheets. As temperature rising, CoMn-alginate was decomposed into in-situ grown nanoparticle. The thermal decomposition temperature of AP was significantly reduced by 122.9 ℃. Possible synergistic mechanism for the thermal decomposition of AP was proposed. Abstract: An excellent material for thermal decomposition of ammonium perchlorate (AP) is urgently required. Herein, inspired by natural biopolymer, we prepared CoMn–alginate/AP composite by air atomization method. The results clearly indicated that the bimetallic CoMn–alginate had a 3D network structure consisting of pores and some thin nanosheets. With increasing temperature, the bimetallic CoMn–alginate was decomposed and formed MnCo2 O4 nanoparticles by in situ growth. These MnCo2 O4 nanoparticles had better catalytic activity for thermal decomposition of AP. In addition, we investigated the effect of using different mass ratios of AP and sodium alginate (SA) and different molar ratios of Co(NO3 )2 and Mn(NO3 )2 on catalytic thermal decomposition of AP. Notably, the thermal decomposition temperature was decreased by 122.9 °C. Furthermore, we also proposed a possible synergistic mechanism. All the results indicated that the bimetallic CoMn–alginate had a greater synergistic effect on thermal decomposition of AP.